EVALUATION OF THE IMPLEMENTATION TIME OF BUILDING CONSTRUCTION PROJECTS WITHIN THE NATIONAL POLICE - Muhamad Suripto; Mardi Aman (Jurnal Ekonomi, 2023)
The development process requires relationships between the parties involved in a project, generally differentiated into functional relationships, namely patterns of relationships related to these parties’ functions and formal working relationships, namely patterns of relationships related to cooperation between the parties. parties involved in a construction project confirmed by a contract document. The method in this research is qualitative. The results in this study increased the duration of the work and several days of the project there was no work because the foundation work was on a critical trajectory and there was a need for cooperation and communication within the Police. If one job has experienced delays, to catch up on delays so that the project does not experience delays as a whole is to speed up the superstructure work. One way is to provide formwork for more floors, so that the superstructure work can be completed more quickly with good management at the National Police level.